The 1,3-dipolar cycloaddition reaction in the functionalization of carbon nanofibers - Araújo, R. F. (2007)
Carbon nanofibers were functionalized using a reaction scheme described in the literature for 1,3- dipolar cycloaddition of azomethine ylides generated in situ by the condensation of an -amino acid and an aldehyde. The reagents used were Z-Gly-OH and paraformaldehyde. Their reaction with carbon nanofibers was studied as a solid mixture by controlled heating in the DSC. An oxazolidinone intermediate was formed as the major product. Z-Gly-OH and paraformaldehyde were also reacted with a model compound (anthracene) in DMF solution leading to the formation of a considerable amount of anthraquinone. These studies suggested that, under the conditions investigated, the 1,3- dipolar cycloaddition reaction was not favoured, and the main result of functionalization was the formation of quinone-type groups as a consequence of an oxidation process.